Effects of over-expressing resistin on glucose and lipid metabolism in mice - Liu, You (Zhejiang University Press, 2008)

(untitled)
Resistin, a newly discovered peptide hormone mainly secreted by adipose tissues, is present at high levels in serum of obese mice and may be a potential link between obesity and insulin resistance in rodents. However, some studies of rat and mouse models have associated insulin resistance and obesity with decreased resistin expression. In humans, no relationship between resistin level and insulin resistance or adiposity was observed. This suggests that additional studies are necessary to determine the specific role of resistin in the regulation of energy metabolism and adipogenesis. In the present study, we investigated the effect of resistin in vivo on glucose and lipid metabolism by over-expressing resistin in mice by intramuscular injection of a recombinant eukaryotic expression vector pcDNA3.1-Retn encoding porcine resistin gene. After injection, serum resistin and serum glucose (GLU) levels were significantly increased in the pcDNA3.1-Retn-treated mice; there was an obvious difference in total cholesterol (TC) level between the experiment and the control groups on Day 30. In pcDNA3.1-Retn-treated mice, both free fatty acid (FFA) and high density lipoprotein (HDL) cholesterol levels were markedly lower than those of control, whereas HDL cholesterol and triglyceride (TG) levels did not differ between the two groups. Furthermore, lipase activity was expressly lower on Day 20. Our data suggest that resistin over-expressed in mice might be responsible for insulin resistance and parameters related to glucose and lipid metabolism were changed accordingly.